Tajikistan Policy Note : Enhancing the Development Impact of Remittances - World Bank (Washington, DC, 2014)
Remittances have played an important role as one of the drivers of Tajikistan's robust economic growth during the past several years. The volume of official remittances has significantly increased since 2001 and now represent close to 12 percent of GDP (2004). Remittances have become the most important source of external financing for the balance of payments, have increased incomes, and as a result helped reduce poverty. Recognizing their importance, the Tajikistan authorities have sought to sustain remittance flows. However, anecdotal evidence indicates that migrants are not sufficiently integrated into the Tajikistan financial system, much less that of the destination countries (e.g. Russia). This Policy Note has two main objectives: (1) to expand knowledge of the size of remittances, their sending mechanisms (especially through formal channels), and their use; and (2) to propose policy recommendations to enhance the development impact of remittances. The report is organized into six sections, including an Introduction. The sections provide background on migration and remittances related to Tajikistan; discuss the estimation of remittance size and data issues; examine the transfer channels of remittances (their cost, access, and speed), their use, and the impact of remittances by highlighting impediments to the efficiency of remittance transfer services through formal channels, examining the use of remittances by recipient households in Tajikistan, and identifying impacts of remittances on the economy; and drawing some of the key lessons learned from the international experience that could be considered in the Tajik context. The final section recommends policies to enhance the development impact of remittances taking into account the Tajik context and identifies topics for further research.